PENINGKATAN PEMAHAMAN MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DENGAN METODE DISKUSI PADA SISWA KELAS VI SDN 002 RAMBAH - Wahyuni wahyuni (STKIP ROKANIA, 2018)
This study aims to improve students' understanding of the material formulation of Pancasila on the subjects of civic education. This type of research is classroom action research. The subjects of the study were the sixth grade students at SDN 002 Rambah, amounting to 27 people. The results showed that in Cycle I Meeting I the average acquisition value is 57.93, while Cycle I Meeting II average value is 65.37. In Cycle II The first meeting of average score was 73.37 in cycle II The average meeting of acquisition value was 80.37. In this cycle students have actively participated in discussions and disciplines in completing tasks, so that students as a whole can understand the material well.